The Effect of Different Grape Varieties and Adding Different Ratios of Mustard Seeds on the Phenolic Compounds, Antioxidant Capacity, and Bioaccessibility Values of Hardaliye under In Vitro Digestion - Ayşe Semra Aksoy; Mustafa Yaman; Muhammet Arıcı (Turkish Journal of Agriculture: Food Science and Technology)
Hardaliye, grape-based fermented beverage, rich in antioxidant phenolic compounds. Bioaccessibility and antioxidant capacity of bioactive compounds in hardaliye, produced using varying amounts of mustard seeds (1%, 1.5%, and 2%) with Merlot and Papazkarası grape varieties, were evaluated under in vitro gastrointestinal digestion conditions. After digestion, Merlot and Papazkarası samples with 2% addition of mustard seed showed significantly higher total phenolic compounds (TPC) (358.48±14.73 and 89.01±2.42 mg GAE/L, respectively) compared to other samples (P<0.05). 2% mustard seed added Merlot samples resulted in the highest 1,1-diphenyl-2-picrylhydrazyl (DPPH) and cupric reducing antioxidant capacity (CUPRAC)  values (19.06±3.91 and 9.96±1.83 mmol TEAC/L, respectively) which differed significantly from other samples (P<0.05). The Merlot sample with 2% addition of mustard seed showed significantly higher TPC, total flavonoid compounds (TFC), DPPH, and CUPRAC bioaccessibility values compared to other Merlot samples (P<0.05). For Papazkarası samples with 2% mustard seed addition, significant differences were observed only in terms of TPC and TFC bioaccessibility values (15.87±2.30% and 15.27±1.29%, respectively) compared to samples with 1% and 1.5% mustard seed addition (P<0.05). The study demonstrated that the bioaccessibility of bioactive compounds in hardaliye can vary depending on the grape variety and to some extent, the use of mustard seed. This suggests that the food matrix and interaction with other food matrices in the environment can affect the stability and bioavailability of bioactive compounds during simulated digestion.